Social Health Status and Its Related Factors in Older Adults - Fatemeh Sadadt Izadi-Avanji; Rasoul Mohseni-Asl; Hamidreza Gilasi (Journal of Holistic Nursing and Midwifery)
Introduction: For successful aging, it is necessary to evaluate social health as a basic component of the health system. Older adults are an increasingly large proportion who are potential candidates for vulnerability in social health. Objective: This study aimed to determine social health and its related factors in older adults referred to urban comprehensive health service centers. Materials and Methods: This cross-sectional study was conducted on 400 older adults referred to urban comprehensive health service centers in Ardabil City, Iran, between February 2021 and April 2022. The multistage sampling method was used to select the older adults. The social health scale for older people was used for data collection. Data were analyzed using an independent t-test, one-way analysis of variance, the Tukey post hoc test, the Pearson correlation coefficient, and linear regression with a stepwise method. Results: The Mean±SD age of the participants was 69.49±7.16 years. The mean score of social health was 57.27±8.7, and for subscales of social support, social adjustment, and perceived environment resource were 30.16±5.9, 15.15±4.14, and 11.95±2.83, respectively. Multivariate analysis showed that marital status (B=4.68, 95% CI, 2.82%-6.54%, P=0.001), education (B=-2.89, 95% CI, -4.87% to -0.9%, P=0.004), job (B=-2.15, 95% CI, -4.1% to -0.21%, P=0.03), income (B=1.48, 95% CI, 0.63%-2.89%, P=0.04), visiting exhibitions (B=4.69, 95% CI, 2.39%-6.98%, P=0.001), and recreational or fun activities (B=-2.36, 95% CI, -3.99% to -0.72%, P=0.005) were predictors of social health in older adults (R2=20%). Conclusion: The social health of older adults is moderate. Our study showed that several factors would influence social health. Healthcare providers should plan necessary interventions to enhance the social health of older adults.